The legal base for collective bargaining in private higher education - Michele L. Ramsey (Educational Considerations, 1979)
In labor relations, the impact is judged more than the intent. There are few innocuous mistakes. The best course for both administrators and faculty members, regardless of their individual desire to engage in collective bargaining, is to be knowledgeable about the topic.